2001
DOI: 10.1183/09031936.01.99102601
|View full text |Cite
|
Sign up to set email alerts
|

Serum Clara cell protein (CC16), a marker of the integrity of the air-blood barrier in sarcoidosis

Abstract: Serum Clara cell protein (CC16), a marker of the integrity of the air-blood barrier in sarcoidosis. C. Hermans, M. Petrek, V. Kolek, B. Weynand, T. Pieters, M. Lambert, A. Bernard. #ERS Journals Ltd 2001. ABSTRACT: To test the hypothesis that sarcoidosis is associated with an intravascular leakage of lung epithelium secretory proteins, the occurrence and determinants in serum of sarcoid patients of CC16, a small size and readily diffusible lung-specific protein of 16 kDa secreted by bronchiolar Clara cells, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 39 publications
3
41
0
Order By: Relevance
“…For example, increase of BALF surfactant protein A may result from increase of the synthesis and/or release by secreting cells or by impaired clearance by alveolar macrophages, mucociliary transport, degradation, and absorption into the bloodstream. Increased synthesis and/or release are the most plausible mechanisms explaining BALF SP-A increase in patients with sarcoidosis [65]. The analysis of the BALF proteome may, thus be helpful to quantify the overall molecular changes associated with lung injuries but may also offer the possibility to directly monitor therapeutic interventions.…”
Section: Fibrosing Interstitial Lung Diseasesmentioning
confidence: 99%
“…For example, increase of BALF surfactant protein A may result from increase of the synthesis and/or release by secreting cells or by impaired clearance by alveolar macrophages, mucociliary transport, degradation, and absorption into the bloodstream. Increased synthesis and/or release are the most plausible mechanisms explaining BALF SP-A increase in patients with sarcoidosis [65]. The analysis of the BALF proteome may, thus be helpful to quantify the overall molecular changes associated with lung injuries but may also offer the possibility to directly monitor therapeutic interventions.…”
Section: Fibrosing Interstitial Lung Diseasesmentioning
confidence: 99%
“…If purified CC16 is applied to serum, this assay has a detection limit of 0.5 μg/L and an average analytical recovery of 95%. The intra-assay and inter-assay coefficients of variation range from 5 to 10% [15,16]. The sPLA 2 enzyme activity was measured by the hydrolysis of 2-3 H-linoleyl-phosphatidyl-ethanolamine and was expressed as nmol/mL/h hydrolysis [29].…”
Section: Laboratory Assaysmentioning
confidence: 99%
“…However, clinical studies have shown that circulating CC16 rises in various pulmonary diseases characterised by increased epithelial permeability, such as acute respiratory distress syndrome [18], idiopathic interstitial pneumonia [26] and sarcoidosis [12], as well as after exposure to environmental air pollutants [6] or fire smoke [5]. On the basis of this evidence, CC16 has been proposed as a potential, non-invasive, peripheral, blood biomarker specific to the lung injury.…”
mentioning
confidence: 98%